COPING MECHANISMS IN ADOLESCENTS WHO HAVE VULGENT ACNE IN MTS ASSA'ADA CLASS 3 KANDANGAN SAMBENG DISTRICT - Sairozi, Ali (Universitas Airlangga, 2020)
Introduction: Physical conditions in adolescence are a source of changes in self-identity and self-concept, many of which are caused by physical images. As in adolescents who have acne or acne, where this often occurs in adolescents aged 15-19 years in women and 17-21 in men. One of the effects of the occurrence of acne in adolescents is the emergence of coping mechanisms that are adaptive mall. This is reinforced from the results of the initial survey conducted by researchers in grade 3 students at MTs Assa'ada Kandangan, Sambeng District, 10 students obtained data that 7 or 70% of students with acne used a maladaptive coping mechanism and 3 or 30% of students used a mechanism adaptive coping. The purpose of this study was to identify the picture of coping mechanisms in adolescents who have acne vulgaris at MTs Assa'ada class 3 Kandangan Sambeng District.Methods: The design used in this study was descriptive with sampling techniques using total sampling and the instruments used were questionnaires with closed questions to respondents. From the results of the questionnaire data grouping and data tabulation were carried out by descriptive method and transformed in the form of narratives and percentages.Results: The results of the study showed that most respondents had adaptive coping mechanisms. This may be influenced by several factors including: gender and age. Conclusion: The experience factor of the respondents is quite adequate this is because of the time the acne appears itself. If the acne arises the respondent has an effective method or trick in the association to show his confidence. The occurrence of acne that is common in adolescence, then over time teenagers will be able to adjust to the situation, because it is considered normal thing and often occurs in adolescence.